Effect of different operational conditions on the decolorization of molasses spent wash using once developed soil inoculum - Adikane, H. V.; Dixit, J. N. (Biodegradation, 2009)
A stirred vessel coupled with membrane unit containing cellulose acetate (0.45 mu m) membrane was used to study the decolorization of anaerobically digested molasses spent wash (MSW). The soil collected from the MSW disposal site was used as inoculum to study the decolorization without addition of any additives. The same inoculum was used over a period of 163 days at room temperature to study the decolorization of 12.5-50% (v/v) MSW using different operational conditions. The reactor was entered in to the inhibition mode after the feeding of 50% MSW, which was restored 100% without changing any operational condition. The maximum decolorization obtained for 12.5% (v/v) MSW was 77.22 +/- A 0.13%. The decolorization achieved for 25, 37.5, and 50% (v/v) MSW was 70.41 +/- A 0.12, 56.47 +/- A 0.17, and 48.78 +/- A 0.09%, respectively. Increase in the utilization of protein and reducing sugar was observed up to 25% MSW whereas, higher concentration showed decrease in the utilization. Results indicate 63% removal of chemical oxygen demand for 12.5% (v/v) MSW. Membrane flux which was significantly reduced after the feeding of 50% MSW was regenerated without changing the washing procedure, however, 35% decrease in sample flux was observed over the continuous use of membrane for the period of 198 days.
Keywords: Decolorization; Membrane flux; Molasses spent wash; Soil as inoculum; stirred vessel